A Companion to Women in the Ancient World - James, Sharon L. (Blackwell companions to the ancient world, 2012)
Selected by Choice as a 2013 Outstanding Academic TitleAwarded a 2013 PROSE Honorable Mention as a Single Volume Reference/Humanities Social SciencesA Companion to Women in the Ancient Worldpresents an interdisciplinary, methodologically-based collection of newly-commissioned essays from prominent scholars on the study of women in the ancient world.The first interdisciplinary, methodologically-based collection of readings to address the study of women in the ancient worldExplores a broad range of topics relating to women in antiquity, including: Mother-Goddess Theory; Women in Homer, Pre-Roman Italy, the Near East; Women and the Family, the State, and Religion; Dress and Adornment; Female Patronage; Hellenistic Queens; Imperial Women; Women in Late Antiquity; Early Women Saints; and many moreThematically arranged to emphasize the importance of historical themes of continuity, development, and innovationReconsiders much of the well-known evidence and preconceived notions relating to women in antiquityIncludes contributions from many of the most prominent scholars associated with the study of women in antiquity Sharon L. Jamesis Associate Professor of Classics at the University of North Carolina at Chapel Hill. She is the author of Learned Girls and Male Persuasion: Gender and Reading in Roman Love Elegy(2003), and the forthcoming Women in Greek and Roman New Comedy. Sheila Dillonis Associate Professor in the Department of Art, Art History Visual Studies at Duke University with a secondary appointment in the Department of Classical Studies. She is the author ofAncient Greek Portrait Sculpture(2006), and The Female Portrait Statue in the Greek World(2010).